Genesis of human rights and freedoms of citizens - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article is examine the problems of legal definition of rights and freedoms. Paid attention to the historical development of such categories as: "man", "person", "personality". Shown that the fonnation and legal providing of citizens’ rights in different countries at different times depended on the level of state development in general and the right particular. Also referred to the need to take into account the objective circumstances in Ukraine in the process of legal regulation of civil rights.